At work in the Informal economy of India: a perspective from the bottom up - "Breman, Jan" (New Delhi, 2013)
While discussing labor being pushed out of agriculture, Jan Breman analyses why, when and how this massive shift in production and employment came about. The book results from his anthropological fieldwork conducted in Gujarat on record as the state with the highest rate of economic growth spanning over five decades. Although centered on one Indian state, the issues highlighted have much wider resonance, as South Asia is at the epicenter of the informal economy. The book is divided into two parts. The first part discusses the past and present path of capitalism and dwells on the abominable condition of the unorganized workforce and the commodification of labor. The second part comprises of the author's 10 previously published studies based on his long grounded research focused on the informal economy and elaborates on themes and issues introduced in the first part of the book. This part also familiarizes the reader with the concept of informality and its ramifications. The book examines the labor regime that, in the past decades, has become dominant in the world at large and is framed in the concept of the informal economy.
Keywords: India-Informal sector-Gujarat